Talasemia : sebuah Tinjauan Pustaka - I Dewa Ayu Natih Canis Paloma (Department of Pharmacy, Bumigora University, 2023)
Thalassemia is a genetic disorder in red blood cells, so sufferers must receive blood transfusions throughout their lives. A diagnosis is made based on anamnesis, physical examination, and supporting examinations. In general, blood transfusions are performed. Depending on the patient's condition, management may differ for each individual.